Bioscience entrepreneurship in Asia : - Teng, P. S. (World Scientific, 2008)
This potential will be further enhanced by the declining capacity of the world s oil reserves to provide hydrocarbons for fuel and materials, and plants will become more important as bio-factories for basic ingredients to sustain human societies.